Return to work after maternity leave: the role of support policies on work attitudes of women in management positions. Issue 1 (26th August 2020) - Costantini, Arianna; Dickert, Stephan; Sartori, Riccardo; Ceschi, Andrea
Abstract : Purpose: This study aims to expand our knowledge on the processes through which work–family policies relate to work–family conflict as well as work–related attitudes among women in management positions returning to work after maternity leave. Design/methodology/approach: A total of 238 women in management positions who recently have returned to work after maternity leave completed a self-reported questionnaire. Findings: Results show that the availability of policies was either directly or indirectly positively related to work attitudes among female managers. Also, findings show that work–family conflict partially mediates the relationship between the availability of communication and psychological support and flexible time management policies with work engagement, and policy availability moderates the relationship between work–family conflict and work engagement. Originality/value: Managers have a crucial role in conveying the value of work–family policies and in creating a culture supporting the management of work and family. By investigating the processes underlying the role of work–family policies in influencing work attitudes of women in managerial positions, this study sheds light on how the awareness of the available policies might be an important determinant of work-related well-being and organizational commitment.